Preferred attributes of sportswear products among South African females - Hutcheon, Michelle (My University, 2018)
Sports bras, as a subcategory of sportswear, represents a large and growing marketing opportunity for manufacturers. It is believed that the manufacturer who wins the hearts and minds of consumers in the sports bra category, will also gain the entire shopping basket of the female athletic shopper. A sports bra is an apparel product composed of physical attributes. When considering a product purchase, consumers compare and contrast alternative products through the evaluation of product attribute combinations. Preferences for the apparel items may depend on the joint influence of these product attributes. This study aims to determine the relative importance of the product attributes that influence the buying behaviour of sports bras. A second objective is to segment the market based on the relative importance of the attribute rankings, and a third objective is to understand the consumer channel preferences when purchasing sports bras. The identification of the relative importance placed on product attributes will assist manufacturers to enhance their marketing strategies and new product development efforts. Data was collected through an online and face-to-face survey using a structured questionnaire from a convenience sample of 326 female respondents. Conjoint analysis was performed on the data to determine the relative importance of the product attributes. A cluster analysis was then conducted on the results of the conjoint study to determine whether differentiated consumer segments exist. The channel preferences were determined using a distribution-fitting approach with ANOVA tests. The results show that South African females consider brand as the most important product attribute, followed by fit, price, function and design/style (the latter two attributes show no significant difference in ranking). The cluster analysis revealed that females display relatively homogenous behaviour and prefer speciality sports stores when purchasing sports bras
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2018